Pengaruh Senam Prolanis terhadap Tekanan Darah Pasien Hipertensi Peserta Prolanis di Puskesmas Guntur I - Azka Milcha Salatin; Nutrisia Nu’im Haiya; Muh Aspihan (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Hypertension is a non-communicable disease that is the leading cause of death worldwide because it can trigger serious complications such as heart disease and stroke. Guntur I Community Health Center is one of the areas with a high incidence of hypertension. One non-pharmacological intervention to control blood pressure is through regular physical activity such as Prolanis exercise. This study aims to analyze the effect of Prolanis exercise on blood pressure reduction in hypertensive patients at the Guntur I Community Health Center. This study used a quantitative research design with a one-group pre-test and post-test design. Research population: all 50 hypertensive patients participating in Prolanis at the Guntur I Community Health Center, with a sampling technique using total sampling. Research instruments included the Prolanis exercise SOP, digital tensiometer, and observation sheet. Data analysis: Data were processed using bivariate statistical tests to determine the significance of the intervention's effect. The results of the study showed a significant decrease in average blood pressure after participating in Prolanis exercise. The average systolic blood pressure decreased from 157.40 mmHg to 148.60 mmHg. Meanwhile, the average diastolic blood pressure decreased from 92.80 mmHg to 84.00 mmHg. Statistical test results showed a p-value = 0.000 (p < 0.05), so it can be concluded that there is a significant effect between participation in Prolanis exercise and a decrease in blood pressure.